Characterization of multispectral aerial images of sugarcane - Solano, Agustín; Schneider, Gerardo; Kemerer, Alejandra Cecilia; Hadad, Alejandro Javier (IOP Science, 2023)
Trabajo presentado al 19th Argentinean Bioengineering Society Congress (SABI 2013), 4–6 September 2013, Tucumán, Argentina